Analisis Karakteristik Kuat Tekan Beton Mutu Tinggi Dengan Penggunaan Satu Fraksi Agregat Terhadap Pesentase Penambahan Sikament NN - Rabbani Anugrahrosah, Muhammad; Novan, Andre; Azhari (Jurnal Vokasi Manajemen Dan Rekayasa Infrastruktur Sipil, 2024)
Concrete is a construction material that has characteristics including; compressive strength, workability, durability and so on are used because they have the advantage of being quite durable constituent materials. Concrete has a high compressive strength value which is required to be greater than or equal to 41.4 MPa listed in SNI 03-6468-2000. The water cement factor (FAS) value is the ratio of the weight of water to the weight of cement which greatly influences the quality/compressive strength of concrete. The more air means the greater the FAS, the easier the concrete is to work with, but the quality decreases. The use of Superplasticizer Admixture, a type of water reduction, is expected to increase the compressive strength of concrete with a good level of workability. In this research, the additional ingredient Sikament NN was produced by PT. Sika Indonesia which is a Type F Superplasticizer with varying doses, namely 1.0%, 1.2%, 1.4%, 1.6% and 1.8% of the cement weight. The maximum concrete compressive strength value obtained was 43.97 MPa at a Sikament NN dosage of 1.4% of the cement weight, which is the optimal Sikament NN dosage for compressive strength values. At this dose, the concrete slump value is 8.2 cm. The maximum slump value obtained was 24.08 cm in concrete with a Sikament NN dosage of 1.8% by weight of cement.